CD8+ T Cell-Mediated Neuronal Dysfunction and Degeneration in Limbic Encephalitis - Ehling, Petra; Melzer, Nico; Budde, Thomas; Meuth, Sven G. (Frontiers in Neurology, 2015)
Autoimmune inflammation of the limbic grey matter structures of the human brain has recently been identified as major cause of mesial temporal lobe epilepsy with interictal temporal epileptiform activity and slowing, progressive memory disturbances, as well as a variety of other behavioral, emotional and cognitive changes. Magnetic resonance imaging exhibits volume- and signal-changes of the amygdala and hippocampus, and specific anti-neuronal antibodies binding to either intracellular or plasma membrane neuronal antigens can be detected in serum and cerebrospinal fluid. While effects of plasma cell-derived antibodies on neuronal function and integrity are increasingly becoming characterized, potentially contributing effects of T cell-mediated immune mechanisms remain poorly understood. CD8+ T cells are known to directly interact with major histocompatibility complex class I (MHC I) expressing neurons in an antigen-specific manner. Here, we summarize current knowledge on how such direct CD8+ T cell-neuron interactions may impact neuronal excitability, plasticity and integrity on a single cell and network level and provide an overview on methods to further corroborate the in vivo relevance of these mechanisms mainly obtained from in vitro studies.